DNA sequence variants in the LOXL1 gene are associated with pseudoexfoliation glaucoma in a U.S. clinic-based population with broad ethnic diversity - Miller Joan W; del Bono Elizabeth; Kim Ivana; DeAngelis Margaret M; Chen Teresa; Rhee Douglas; Grosskreutz Cynthia L; Pasquale Louis; Fan Bao; Li Tiansen; Haines Jonathan L; Wiggs Janey L (BMC, 2008)
Abstract Background Pseudoexfoliation syndrome is a major risk factor for glaucoma in many populations throughout the world. Using a U.S. clinic-based case control sample with broad ethnic diversity, we show that three common SNPs in LOXL1 previously associated with pseudoexfoliation in Nordic populations are significantly associated with pseudoexfoliation syndrome and pseudoexfoliation glaucoma. Methods Three LOXL1 SNPs were genotyped in a patient sample (206 pseudoexfoliation, 331 primary open angle glaucoma, and 88 controls) from the Glaucoma Consultation Service at the Massachusetts Eye and Ear Infirmary. The SNPs were evaluation for association with pseudeoexfoliation syndrome, pseudoexfoliation glaucoma, and primary open angle glaucoma. Results The strongest association was found for the G allele of marker rs3825942 (G153D) with a frequency of 99% in pseudoexfoliation patients (with and without glaucoma) compared with 79% in controls (p = 1.6 × 10-15; OR = 20.93, 95%CI: 8.06, 54.39). The homozygous GG genotype is also associated with pseudoexfoliation when compared to controls (p = 1.2 × 10-12; OR = 23.57, 95%CI: 7.95, 69.85). None of the SNPs were significantly associated with primary open angle glaucoma. Conclusion The pseudoexfoliation syndrome is a common cause of glaucoma. These results indicate that the G153D LOXL1 variant is significantly associated with an increased risk of pseudoexfoliation and pseudoexfoliation glaucoma in an ethnically diverse patient population from the Northeastern United States. Given the high prevalence of pseudooexfoliation in this geographic region, these results also indicate that the G153D LOXL1 variant is a significant risk factor for adult-onset glaucoma in this clinic based population.